EFEKTIVITAS KAMPUNG KELUARGA BERENCANA (KB) GUNA MEWUJUDKAN KELUARGA KECIL MANDIRI - Quartika, Fitrilia; Mona, Silvia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
The rapidly growing number of the population has become our government longtime concern thus the KB (KeluargaBerencana) (family planning) program is introduced. However, the indifference and the lack of knowledge on the program among the general public has imperiled its effectiveness. To achieve the goal, the government via BKKBN (BadanKependudukandanKeluargaBerencanaNasional) (National Population and Family Planning Board)has the initiative by optimizing the role of local government in advancing the program through the KB Kampongs. This research aims to discover the effectiveness of the family planning kampong program in initiating the concept of independent small family. The research design employs descriptive analysis with qualitative approach that was conducted in Kelurahan (urban community) TanjungUnggat in May 2019. The research respondents are BKKBN, local government, and the society of the KB kampong, using interviews and observations as the medium. From the interview sessions, in order to assess the effectiveness of the program, it is revealed that the respondents especially the officials and stakeholders in majority are well-informedand aware about the program and the goal of the program, and it is worth noted that the continuum of its implementation is as planned and in progress. However, the immediate result is still far from perfect, in part the society due to the indifference but the programoverall shows positive progress and the society begin to willingly participate as they grow and understand better. In conclusion, as the result suggests, the KB Kampong program in promoting the concept of independent small family has not yet reached its success or effectiveness. In suggestion, the program needs to be pushed on and popularized to gain more exposures, for example, via seminaries and public talks, and any similar future research is expected to give reports on its progress.